How do firms adjust to rises in the minimum wage? Survey evidence from Central and Eastern Europe - Katalin Bodnár; Ludmila Fadejeva; Stefania Iordache; Liina Malk; Desislava Paskaleva; Jurga Pesliakaitė; Nataša Todorović Jemec; Peter Tóth; Robert Wyszyński (IZA Journal of Labor Policy, 2018)
We study the transmission channels for rises in the minimum wage using a unique firm-level dataset from eight Central and Eastern European countries. Representative samples of firms in each country were asked to evaluate the relevance of a wide range of adjustment channels following specific instances of rises in the minimum wage during the recent post-crisis period. The paper adds to the rest of literature by presenting the reactions of firms as a combination of strategies and evaluates the relative importance of those strategies. Our findings suggest that the most popular adjustment channels are cuts in non-labour costs, rises in product prices, and improvements in productivity. Cuts in employment are less popular and occur mostly through reduced hiring rather than direct layoffs. Our study also provides evidence of potential spillover effects that rises in the minimum wage can have on firms without minimum wage workers.
Keywords: D22; E23; J31; 330; Minimum wage; Adjustment channels; Firm survey